Study of the phenolic compounds of the dry extract of Thymus crebrifolius using a combined HPLC–UV and HPLC-ESI-MS/MS method - Ivasenko, S.A.; Shakarimova, K.K.; Bokayeva, A.B.; Marchenko, A.B.; Lavrinenko, A.V.; Kolesnichenko, S.I. (KU Publ., 2021)
In world practice interest in herbal medicines is noticeably increasing every year. From this point of view, plants of the Thymus L. genus of the Lamiaceae family are of undoubted interest. Previously we have obtained a dry extract from the aerial part of an endemic plant of the flora of Kazakhstan Thymus crebrifolius Klokov for the first time by double extraction of raw plant materials with 70% ethanol using ultrasound. Dry extract of Thymus crebrifolius has a wide spectrum of antimicrobial activity, including against Helicobacter pylori, while it is not toxic, and can be used as an antimicrobial agent. The article presents the results of a study of the composition of phenolic compounds of dry extract of Thymus crebrifolius using a combined HPLC-UV and HPLC-MS/MS method. 12 phenolic compounds have been identified and quantified in the dry extract of Thymus crebrifolius. Four of them are phenolic acids, and eight are flavonoids. The dominant phenolic compounds are luteolin-7-O-glucoside (109.00 mg g−1), rosmarinic acid (30.98 mg g−1), naringenin (24.84 mg g−1), epicatechin (9.98 mg g−1), myricetin (6.15 mg g−1) and gallic acid (3.41 mg g−1). The results of chromatographic analysis will be used to standardize drugs based on dry extract of Thymus crebrifolius.
ЖТСХ–УК және ЖТСХ-МС/МС аралас әдісін қолдануымен Thymus crebrifolius құрғақ сығындысының фенолдық қосылыстарын зерттеу
Изучение фенольных соединений сухого экстракта Thymus crebrifolius c использованием комбинированного метода ВЭЖХ–УФ и ВЭЖХ-MС/MС
Keywords: Thymus crebrifolius Klokov; dry extract; HPLC-UV; HPLC-ESI-MS/MS; phenolic acids; flavonoids; luteolin-7-O-glucoside; rosmarinic acid